1967
DOI: 10.1017/s0021859600017962
|View full text |Cite
|
Sign up to set email alerts
|

The lipolysis and hydrogenation of lipids in the digestive tract of the sheep

Abstract: 1. The flow of digesta in the duodenum and the changes in the lipid composition of ruminal and duodenal digesta of sheep accustomed to receiving hay and oats, hay and palm oil and hay and tallow have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Felinski et al 1964). It is also possible that variations exist between species in the structure and composition of micelles in the intestine, and that these variations may be related to the relatively high intestinal pH, the low concentration of monoglycerides, and the high concentration of phospholipids in the intestine in sheep (Hofmann 1966;Bath and Hill 1967;Garton 1967;Lennox, Lough, and Garton 1968).…”
Section: (E) Effect Of Surgery On Absorption Of Fatty Acidsmentioning
confidence: 99%
“…Felinski et al 1964). It is also possible that variations exist between species in the structure and composition of micelles in the intestine, and that these variations may be related to the relatively high intestinal pH, the low concentration of monoglycerides, and the high concentration of phospholipids in the intestine in sheep (Hofmann 1966;Bath and Hill 1967;Garton 1967;Lennox, Lough, and Garton 1968).…”
Section: (E) Effect Of Surgery On Absorption Of Fatty Acidsmentioning
confidence: 99%
“…Both galactose and glycerol are subsequently metabolized in the rumen to volatile fatty acids. Bath and Hill (1967) confirmed that complete hydrolysis of exogenous glyceridic lipids was effected in the rumen. Using rumen-fistulated animals, they were unable to detect mono-and diglycerides following a fat diet.…”
Section: Metabolism In the Rumensupporting
confidence: 58%
“…Hawke and Robertson (1964) had previously found hydrolysis intermediates (mono-and diglycerides) in the rumen after infusion of linseed oil. However, these results were explained in terms of over loading the rumen with triglyceride (Bath and Hill, 1967).…”
Section: Metabolism In the Rumenmentioning
confidence: 90%
“…Lysolecithin then assumes the role of monoglyceride in micelle formation in the ruminant intestine (Bath and Hill, 1967;Leat and Harrison, 1969). Lennox and Garton (1968) fitted sheep with re-entrant cannulae in different parts of the small intestine to study absorption of long chain fatty acids.…”
Section: Lymphatico-venous Anastomosesmentioning
confidence: 99%